Efektivitas Penggunaan Media Pembelajaran Berbasis Android Terhadap Aspek Kognitif Siswa Tunarungu di SDLB N Pangkalpinang (Studi Kasus Pembelajaran Shalat Kelas 3) - putri, Dian Puspita eka; ratih, ratih (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
The rapid development of information and communication technology provides many benefits to aspects of life, especially the world of education. The sophistication of Android-based mobile phones as a medium of communication and information continues to increase and innovate. So it is hoped that teachers can be more creative in delivering subject matter, especially prayer learning by utilizing Android-based learning media to children with special needs, one of which is deaf students so that it is hoped that student learning outcomes can increase both in cognitive, affective and psychomotor aspects. However, based on observations at SDLB N Pangkalpinang there are still teachers who have not utilized or used Android as a learning medium, these teachers only use image media so that the learning outcomes of deaf students are low in cognitive aspects after the pretest was carried out. The purpose of this study was to test how the effectiveness of Android-based learning media on the cognitive aspects of deaf students in SDLB N Pangkalpinang. used was 8 students with the sampling technique using saturated sampling. The data collection in this study used the pretest and posttest questions, while the data processing used the normality test, homogeneity test, and paired sample T-test with the help of SPSS version 16. After conducting the research, it was concluded that there was a difference in the average between the pretest and posttest, where the average at the pretest was 31.25, while the average at the posttest was 46.25. This means that the average score on the posttest is higher than in the pretest. This is also supported by hypothesis testing, the Sig value is obtained. (2-tailed) of 0.005 <0.05, then H0 is rejected and Ha is accepted, meaning that Android-based learning media is effective on the cognitive aspects of deaf students. However, the value obtained has not reached the KKM value for the subject of Islamic religious education